Anomalous refraction into free space with all-dielectric binary metagratings - Tsitsas, Nikolaos L.; Valagiannopoulos, Constantinos (Physical review research, 2020)
Steering the incoming photonic power toward unusual directions, not predicted by Snell's laws of reflection and refraction, is a fundamental operation behind numerous wavefront engineering applications. In this study, strong anomalous transmission is reported to all-dielectric electrically thin structures comprising only two materials in alternating rectangular posts. These binary metagratings have been thoroughly optimized to support almost perfect negative refraction by suppressing all the rest of diffraction orders; such an effect is found to be very robust with respect to oscillation frequency, incident beam angle, and structural defects. In this way, easy-to-fabricate setups working at different colors of the visible spectrum are determined and may be directly incorporated in various optical integrated systems from lenses and beamformers to field enhancers and power splitters.